Histological comparison between irradiated and non-irradiated breasts in breast reconstruction - Alberto Benedik; Ronan Caputi Silva Dias; Amanda Costa Campos; Carolina Oliveira Paranagua Castro; Marcela Caetano Cammarota; José Carlos Daher (Revista Brasileira de Cirurgia Plástica)
Introduction: The treatment of breast cancer includes not only curative therapies but also breast reconstruction. Radiotherapy, an adjuvant strategy, provides favorable outcomes by reducing the rate of recurrence of the disease. This study aimed to compare histological differences between irradiated and non-irradiated breasts in the same patient. Methods: This is a prospective cohort study of patients undergoing breast reconstruction with prosthesis or expander under pectoralis major muscle flap that compared histological skin patterns, subcutaneous cell tissue, pectoralis major muscle, and implant capsule of irradiated and non-irradiated breasts in paired samples of the same patient. All patients included in this study were irradiated in only one breast. The results of the anatomopathological analysis were compared to clinical findings and intraoperative macroscopic aspects. Results: The study included a total of 7 patients with a mean age of 52.15 years. The main histological findings in the skin and subcutaneous cellular tissue of the irradiated breast were as follows: epidermal hyperplasia, flattening of the papillary layer, atrophy of the skin appendages, vascular congestion in fatty tissue, high density of skin collagen fibers, hyalinization, and reduction of elastic fibers in the deep dermis and unidirectional alignment of collagen fibers. The main histological findings for the capsule and pectoralis major muscle in the irradiated breast were as follows: lower density of elastic fibrosis, perivascular fibrosis, synovial metaplasia, skeletal muscle sequestration at the interface with the capsule, capsular hyalinization, and capsular fribrosclerosis. Conclusion: We found common histological changes in irradiated breasts in most patients. These findings are compatible with the clinical and macroscopic changes observed. This study presents itself as a pilot for the development of further studies investigating the physiopathological mechanisms of the described histological changes.